2019
DOI: 10.1007/s00520-018-4613-3
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experiences of life review therapy combined with memory specificity training (LRT-MST) targeting cancer patients in palliative care

Abstract: Purpose Life review therapy combined with memory specificity training (LRT-MST) is effective in cancer patients in palliative care, but the effect size is moderate. The aim of this qualitative study was to obtain more in-depth knowledge on motivation to start with LRT-MST, experiences with LRT-MST, and perceived outcomes of LRT-MST. Methods Semi-structured interviews were conducted with 20 cancer patients in palliative care who participated in a randomized controlled trial investigating the effect of LRT-MST. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A change in the nurse-patient relationship was also noted and it was deemed to be beneficial [ 146 ]. Further studies exploring the impact of Life Review Therapy (LRT) and Memory Specificity Training (MST) (LRT-MST) were found to improve ego-integrity and despair among cancer patients in palliative care [ 147 ], with qualitative analysis indicating the benefit and acceptance of the intervention among the patients [ 148 ], but no specific effect on the family caregivers [ 148 , 149 ].…”
Section: Resultsmentioning
confidence: 99%
“…A change in the nurse-patient relationship was also noted and it was deemed to be beneficial [ 146 ]. Further studies exploring the impact of Life Review Therapy (LRT) and Memory Specificity Training (MST) (LRT-MST) were found to improve ego-integrity and despair among cancer patients in palliative care [ 147 ], with qualitative analysis indicating the benefit and acceptance of the intervention among the patients [ 148 ], but no specific effect on the family caregivers [ 148 , 149 ].…”
Section: Resultsmentioning
confidence: 99%
“…This type of life review, or reminiscence, activity is considered particularly productive for those in later adulthood 4 and reflects a long tradition of incorporating life review techniques into healthcare (e.g., mental health counseling, nursing, palliative care). [5][6][7][8] While DT is useful for patients of any age, DT's focus on guiding patients to look back over their life experiences may be particularly poignant for patients in the second half of life.…”
Section: Introductionmentioning
confidence: 99%
“…Ego integrity is described as accepting your life cycle as something that had to be, feeling connected to others, and experiencing a sense of wholeness, meaning, and coherence when facing death) [9]. Additionally, reasons to start, experiences, and perceived outcomes were studied via a qualitative approach among patients who underwent LRT-MST [12]. Patients reported positive outcomes on ego integrity and psychological well-being in the here and now, as well as in the nearby future (including end of life).…”
Section: Introductionmentioning
confidence: 99%